Nelder‐Mead–based power optimization for secrecy enhancement in amplify‐and‐forward cooperative relay networks. (2nd May 2019) - Shemi, P.M.; Jibukumar, M.G.; Ali, M.A.
Summary: Cooperative communication based on relaying nodes has been considered as a promising technique to increase the physical layer security (PLS) performance in wireless communications. In this paper, an optimal power allocation (OPA) scheme based on Nelder‐Mead (NM) algorithm is proposed for improving the secrecy rate of amplify‐and‐forward (AF) cooperative relay networks employing cooperative jamming (CJ) scheme. The proposed hybrid jamming scheme allows the source and selected relay to transmit the jamming signal along with the information to confound the eavesdropper. The path selection probability of ant colony optimization (ACO) algorithm is used for selecting the relay for transmission. The performance based on secrecy rate is evaluated for " n " trusted relays distributed dispersedly between the source and destination. Gradient‐based optimization and three‐dimensional exhaustive search methods are used as benchmark schemes for comparison of the proposed power optimization algorithm. The secrecy performance is also compared with conventional AF scheme and CJ scheme without power optimization (EPA). The impact of single and multiple relays on secrecy performance is also evaluated. Numerical results reveal that, compared with the gradient method and exhaustive search algorithm, the proposed power allocation strategy achieves optimal performance. Also, the derived OPA results show a significantly higher secrecy rate than the EPA strategy for both CJ and AF schemes. Abstract : In this paper, an optimal power allocation (OPA) strategy based on Nelder‐Mead algorithm is proposed to improve the secrecy of cooperative networks employing amplify‐and‐forward–based hybrid jamming scheme, in the presence of a passive eavesdropper. For the purpose of comparison, the conventional amplify‐and‐forward scheme and performance with equal power allocation (EPA) strategy are considered as benchmark schemes. The proposed OPA shows better secrecy performance when compared with i) gradient‐based optimization and exhaustive search methods and ii) EPA analysis as well as conventional AF schemes.